2022
DOI: 10.7189/jogh.12.03044
|View full text |Cite
|
Sign up to set email alerts
|

How to co-exist with COVID-19? A health economics explanation based on the Chinese experience

Abstract: Photo: The trade-off between the benefits of life-health-value and the cost of COVID-19 control strategy (designed by the authors, used with permission).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This extrapolation was strongly supported by ARIMA forecasting that predicted a peak of HMFD cases around May 2020 in the absence of NPIs ( Figures 6C , D ). From then on, the dynamic Zero-COVID policy continued until December 2022 ( Figure 6B ) ( Yang and Yu, 2023 ). As shown in the Figures 5 6B , the predicted biennial peak of HFMD incidence did not occur around May 2022 but a low-volatility plateau of HFMD incidence, which might be caused by the constant NPIs during the 2nd outbreak from March 16 to May 6 2022 ( Figure 6B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This extrapolation was strongly supported by ARIMA forecasting that predicted a peak of HMFD cases around May 2020 in the absence of NPIs ( Figures 6C , D ). From then on, the dynamic Zero-COVID policy continued until December 2022 ( Figure 6B ) ( Yang and Yu, 2023 ). As shown in the Figures 5 6B , the predicted biennial peak of HFMD incidence did not occur around May 2022 but a low-volatility plateau of HFMD incidence, which might be caused by the constant NPIs during the 2nd outbreak from March 16 to May 6 2022 ( Figure 6B ).…”
Section: Resultsmentioning
confidence: 99%
“…A national-scale investigation found that these NPIs have substantially reduced the incidence of HFMD in the first wave of COVID-19 ( Zhao et al, 2022 ). Since the first COVID-19 outbreak in most cities of China, NPIs, vaccines and dynamic Zero-COVID policy were implemented to combat SARS-CoV-2 around mainland China till the end of 2022 ( Yang and Yu, 2023 ). However, the impact of these measures on epidemiological and etiologic characteristics of HFMD has not been well-studied.…”
Section: Introductionmentioning
confidence: 99%
“…Various measures have been implemented in response to emergencies such as COVID-19, including isolation from the community, social distancing, reducing crowd, closing school, swift diagnosis, and contact tracing [ 4 7 ]. These interventions fall into two categories: the blocking mode and the mitigation mode [ 8 ]. The former suggests that some countries have focused on paying short-term costs to avoid significant long-term health and economic losses.…”
Section: Introductionmentioning
confidence: 99%
“…From an economic perspective, some scholars argue that the optimal control policy depends on the pandemic’s impact on healthcare resources and the populace [ 7 ]. Meanwhile, others emphasise that it is a balance between the impact on public health consequences and economic growth [ 12 ], or even a trade-off between value of health and the economic cost of implementing control policies [ 8 , 13 ]. Essentially, a greater number of studies centre on the costs associated with pandemic prevention policies, with a reduced number of studies assessing health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…A national-scale investigation found that these NPIs have substantially reduced the incidence of HFMD in the first wave of COVID-19 (13). Since the first outbreak in most cities of China, NPIs, vaccines and dynamic Zero-Covid policy were implemented to combat SARS-CoV-2 around mainland China till the end of 2022 (14). However, the impact of these measures on epidemiological and etiologic characteristics of HFMD has not been well studied.…”
Section: Introductionmentioning
confidence: 99%